DNA METHYLATION AND THE EFFECT ON BREARST CANCER - Ika Kusuma Wardani (Journal of Holistic and Traditional Medicine, 2017)
Nationally, there is a significant increase in the number of breast cancer cases. Breast cancer is a cancer that occurs in breast tissue and is one of the major cancers, mostly attacking the women and also the men, but the probability is very small. There are some epigenetic processes is DNA methylation, histone modifications and chromosome rearrangements and the role of Micro RNA. DNA methylation is most common and is one of the epigenetic control mechanism against hereditary gene expression but does not change the structure of the composition of the DNA bases and are specific to a particular network.This research litertur review aimed to determine the effect of DNA methylation on the characteristics of breast cancer. This research method uses reviewed journals were electronically obtained from ebscohost, medline with full text,cochrane data base,cinahl and google scholar with keywords DNA Methylation,breast cancer,gen mutation. From various studies that have been published from 2000 – 2016. Of articles were found, 7 articles were analyzed. The results of the literature review found that the most common gene mutation or mutations in common are BRCA1 and BRCA2. It said women with mutations in the BRCA1 and BRCA2 80% risk of developing breast cancer. Other gene mutations in particular genes such as MMP group MMP-9 contributes very important for the risk of breast cancer and a high risk of metastasis to lymph node tissue. Approximately 20-30% of women suffering from breast cancer due to their family history of breast cancer and approximately 5-10% are the result of a gene mutation